Influence of Moringa-Enriched Diets on Proximate Composition of Fish Muscle and Feed Formulation - Aml Younes; Basit Abdullah; Sultana Hussien (AlQalam Journal of Medical and Applied Sciences, 2026)
This study aimed to evaluate the effect of dietary inclusion of Moringa oleifera at two levels (30% and 50%) on the proximate chemical composition of fish muscle and experimental diets. A total of three groups were investigated: a control group and two treatment groups fed diets supplemented with Moringa at 30% and 50%, respectively. Proximate analysis included protein, fat, moisture, ash, carbohydrates (in fish muscle), and fiber (in diets). The results revealed that the proximate composition of fish muscle showed no statistically significant differences among groups (P > 0.05). Protein content slightly increased from 18.63 ± 1.95% in the control group to 19.32 ± 0.67% and 20.96 ± 0.42% in the Moringa 30% and 50% groups, respectively. Fat content decreased from 7.67 ± 1.35% (control) to 4.86 ± 0.19% and 4.96 ± 0.92% in treated groups. Moisture content remained relatively stable (71.27 ± 0.12%, 71.45 ± 0.24%, and 70.87 ± 0.26%), while ash content showed slight variation (2.11 ± 0.35%, 3.49 ± 0.50%, and 2.71 ± 0.55%). Carbohydrate levels were low across all groups, ranging from 0.50 ± 0.10% to 0.79 ± 0.09%. In contrast, the proximate composition of the experimental diets exhibited highly significant differences (P < 0.001). Protein content decreased from 30.12 ± 0.49% in the control diet to 22.02 ± 0.09% and 21.25 ± 0.15% in Moringa 30% and 50% diets, respectively. Fat content increased markedly from 2.70 ± 0.03% to 25.43 ± 0.17% and 35.41 ± 0.32%. Moisture content decreased from 10.50 ± 0.11% to 8.78 ± 0.02% and 6.86 ± 0.06%, while ash content declined from 6.28 ± 0.04% to 3.51 ± 0.06% and 3.96 ± 0.02%. Fiber content increased significantly from 3.63 ± 0.01% (control) to 4.38 ± 0.01% and 4.19 ± 0.014% in the treated diets. In conclusion, the inclusion of Moringa oleifera at 30% and 50% levels significantly altered the nutritional composition of the diets, particularly increasing fat and fiber while reducing protein and moisture content. However, these dietary changes did not significantly affect the proximate composition of fish muscle. These findings suggest that Moringa can be incorporated into fish diets without adverse effects on muscle nutritional quality, despite notable modifications in feed composition.